Success Secrets of the Social Media Marketing Superstars - Corey Duysen (Journal of Applied Communications, 2012)
Book Review: Success Secrets of the Social Media Marketing Superstars by Mitch Meyerson.
Keywords: Success; Social Media; Marketing; Superstars